Economic impact of climate change on agricultural sector: a review - Syed Ali Fazal; Sazali Abdul Wahab (2013)
Global warming is the most serious environmental threat of the 21st century. Extreme changes in global temperature over the last few decades have caused devastating natural disasters have immensely impacted on the agricultural sector as agricultural production is highly dependent on weather, climate and water availability, and is adversely affected by weather-and climate related disasters. This review paper summarizes the recent studies focused on (a) understanding and measuring the effect of climate change on the agricultural sector and (b) recent inventions and adaptations to cope up with the negative effects of climate change. The paper attempts to review how climate and agriculture is interrelated. It illuminates the vulnerability of the agricultural sector that depends highly on the climatic variables, like rainfall and temperatures. The exploration of climatic variations in this paper reveals the estimated economic costs of climate change on agricultural productivity of different regions and also gives an insight into how these climatic challenges at present and future can be best tackled in order to maximize agricultural output which in turn is the backbone of food sustainability of the nations worldwide